Preparation and Investigation of Intelligent Polymeric Nanocapsule for Enhanced Oil Recovery - Shi, Fang (Materials (Basel), 2019)
Micro-/nanomotors colloidal particles have attracted increasing interest as composite surfactants, owing to the combined advantages of both Janus solid surfactants and micro-/nanomotors. Here we put micro-/nanomotors colloidal particles into hollow polymeric micro-encapsulates. An intelligent polymeric nanocapsule was prepared for enhanced oil recovery by the self-assembly method. The particle size range of the polymeric capsule can be controlled between 20 to 1000 nm by adjusting the cross-linking thickness of the capsule’s outer membrane. The average particle size of polymeric capsules prepared in the study was 300 nm. The structure and properties of the Intelligent polymeric nanocapsule was characterized by a wide range of technics such as Fourier transform infrared spectroscopy, scanning electron microscopy by laser diffraction, fluorescence microscopy, pendant drop tensiometer, laser particle size instrument, and interface tension analyzer. It was found that the intelligent polymeric nanocapsule exhibited significant interfacial activity at the oil-water interface. When the Janus particles’ concentration reached saturation concentration, the adsorption of the amphiphilic nanoparticles at the interface was saturated, and the equilibrium surface tension dropped to around 31 mN/m. When the particles’ concentration reached a critical concentration of aggregation, the Gibbs stability criterion was fulfilled. The intelligent polymeric nanocapsule system has a better plugging and enhanced oil recovery capacity. The results obtained provide fundamental insights into the understanding of the assembly behavior and emulsifying properties of the intelligent polymeric nanocapsule, and further demonstrate the future potential of the intelligent polymeric nanocapsule used as colloid surfactants for enhanced oil recovery applications.